Variation in seed transmission of cowpea viruses between single and multiple infections - Ogunsola, K.E.; Kumar, P.L. (2024)
Seed transmission (ST) plays an important role in virus dispersion and disease epidemiology. Many viruses infecting cowpea are known to be seed-transmitted. This study evaluated the rate of virus ST in cowpea varieties inoculated under screenhouse conditions (SC) with bean common mosaic virus-blackeye cowpea mosaic strain (BCMV-BlCM), Southern bean mosaic virus (SBMV) and cucumber mosaic virus (CMV) under single and multiple-infections. Up to 50 seeds harvested from the virus-infected plants of each variety per treatment were used for the grow-out test under insect-proof SC. Data were recorded on seed germination (SG), symptoms in seedlings, and virus ST. The leaf samples were tested for viruses by enzyme-linked immunosorbent assay (ELISA) and reverse-transcription polymerase chain reaction (RT-PCR). The SG rate was 78 ± 2.8–100 ± 0% in all treatments. A total of 1.5% of 1,604 seedlings infected singly showed symptoms, whereas in diagnostics testing, viruses were detected in 2.6% of plants, indicating occurrence of asymptomatic ST. The highest rate of transmission observed for single infections was 17% CMV in IT98K-133–1-1, 17.1% BCMV-BlCM in IT98K-503–1, and 2.3% SBMV in IT99K-1060. The highest CMV frequency under coinfection was 22.2% in plants inoculated (PI) with SBMV + CMV, 4.2% for BCMV-BlCM in PI with BCMV-BlCM + CMV and 2.3% for SBMV in PI with BCMV-BlCM + SBMV + CMV. This study indicated high variation in the rates of ST based on cultivar and virus type, and for each virus under mixed-infection conditions. Diagnostic confirmation detected a higher percentage of seed-transmitted viruses compared to visual assessment, warranting the need for diagnostics for the reliable detection of seed-transmitted viruses.